Handbook of finance. - Fabozzi, Frank J. (Wiley, 2008)
Volume III Valuation, Financial Modeling, and Quantitative Tools contains the most comprehensive coverage of the analytical tools, risk measurement methods, and valuation techniques currently used in the field of finance. It details a variety of concepts, such as credit risk modeling, Black-Scholes option pricing, and Monte Carlo simulation, and offers practical insights on effectively applying them to real-world situations. Incorporating timely research and in-depth analysis, the Handbook of Finance is a comprehensive 3-Volume Set that covers both established and cutting-edge theories and developments in finance and investing. Other volumes in the set: Handbook of Finance Volume I: Financial Markets and Instruments and Handbook of Finance Volume II: Investment Management and Financial Management."